Carbohydrate dependence during hard-intensity exercise in trained cyclists in the competitive season: importance of training status - Manetta, J.; Brun, J. F.; Maimoun, L.; Galy, O.; Coste, O.; Maso, F.; Raibaut, J. L.; Benezis, C.; Lac, G.; Mercier, J. (International Journal of Sports Medicine, 2002)
To test the hypothesis that intensive endurance training increases CHO utilisation during hard-intensity exercise, seven competitive road cyclists (Cy) performed three 50-min steady-state exercise tests on a cycle ergometer above their ventilatory threshold (+ 15 %) over the course of a cycling season (January [ET1], May [ET2] and September [ET3]). We compared the data with the baseline values of seven sedentary controls (Sed). CHO oxidation in Cy was higher in ET2 and ET3 than in ET1 (p < 0.05), was lower in ET3 than in ET2 (p < 0.05) and was higher in Cy than in Sed only in ET2 (p < 0.05). Lactate kinematics were lower in Cy than in Sed in all conditions (p < 0.05), but in Cy they were lower in ET2 than in ET1 and higher in ET3 than in ET2 (p < 0.05). Race performance was impaired and the overtraining score was increased at ET3 in comparison with ET2 (p < 0.05). We conclude that competitive cyclists increase CHO oxidation during hard-intensity exercise over the course of a season, but show a decline by the end of the season in association with the appearance of an overtraining state. Thus, well-trained cyclists develop a CHO dependence, which is modified with training status.